EFEKTIVITAS METODE WAFA SEBAGAI INOVASI DALAM PEMBELAJARAN MEMBACA AL-QUR’AN DI TPQ AL-IKHLASH PALA’AN NGAJUM MALANG - Achadah, Alif; Aziza, Ilma Fahmi; Hasanah, Siti Muawanatul (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2020)
In Islamic religious education, the Qur'an is a source that is used as the foundation of the Islamic religion. Therefore, the Qur'an has an urgent position in guiding and directing people in their daily lives. However, there is a large gap between the importance of reading the Qur'an with the ability to read the Qur'an in Muslim communities in Indonesia. . The Chancellor of the al-Qur'an Institute of Higher Education (PTIQ) Jakarta, Nazaruddin Umar assessed that people who are illiterate al-Qur'an are still high in Indonesia. therefore it is necessary to apply effective and innovative methods of learning the the al-Qur'an. The supporting factors for the application of the waqa method include: the material taught is not much different from the material that has usually been studied, the TPQ Al-Ikhlash assistants help researchers during the process of applying the "Wafa" method at TPQ Al-Ikhlash, the students are orderly and cooperative during the experimental activities. This is certainly very helpful in carrying out the activities of teaching the Koran with the "Wafa" method. While the inhibiting factors for the application of the "Wafa" method include: Santri in one class are 42 children. This is certainly too much because learning the Qur'an is ideally done in small classes. Learning time becomes insufficient because of the sufficient quantity of students.